Effect of Mexico's vaccination program on Covid-19 cases, hospitalizations, and deaths among older adults in Mexico City - Natalie C Gasca; Jose Reyes-Garza; Susana Lozano-Esparza; Pedro Orozco-del Pino; Antonio Olivas-Martinez; Ernesto Ulloa-Pérez; Alfredo Garbuno-Inigo; Jesús Arroyo (Instituto Nacional de Salud Pública, 2022)
Objective. To characterize the impact of Mexico's Covid-19 vaccination campaign of older adults. Materials and methods. We estimated the absolute change in symptomatic cases, hospitalizations and deaths for vaccine-eligible adults (aged >60 years) and the relative change compared to vaccine-ineligible groups since the campaign started. Results. By May 3, 2021, the odds of Covid-19 cases among adults over 60 compared to 50-59 year olds decreased by 60.3% (95%CI: 53.1, 66.9), and 2 003 cases (95%CI: 1 156, 3 130) were avoided. Hospitalizations and deaths showed similar trends. Conclusions. Covid-19 events decreased after vaccine rollout among those eligible for vaccination.